Micorrizas arbusculares en plantines de Alnus acuminata (Betulaceae) inoculados con Glomus intraradices (Glomeraceae) - Becerra, Alejandra Gabriela (2007)
Arbuscular mycorrhizas in Alnus acuminata (Betulaceae) seedlings inoculated with Glomus intraradices (Glomaceae). This work described for the first time the arbuscular mycorrhiza (AM) development in A. acuminata Kunth «andean alder» with G. intraradices Schenk & Smith. Seedlings of A. acuminata were inoculated with root fragments of Medicago sativa L. colonized by G. intraradices in a greenhouse. The Arum-type and AM colonization are described in A. acuminata seedlings. The presence of arbuscules in A. acuminata cortical cells define a functional symbiosis.